Implementasi Design Thinking pada UI/UX Bank Sampah Digital Banjarejo Berbasis Android - Rahendra Firman Sunartama; Pristi Sukmasetya; Maimunah Maimunah (STMIK Budi Darma, 2023)
Garbage is the main cause of environmental pollution. Every year the amount of waste will continue to increase if it is not managed properly and correctly. One alternative solution for managing waste is the establishment of a waste bank as a container to accommodate existing waste. One of the villages that have implemented a waste bank system is Banjarejo Village, Magelang Regency. In this globalization era, the waste bank is not done manually but through an application to facilitate the waste bank management process. Therefore, a waste bank application is needed to increase efficiency, facilitate transactions and increase community participation. In this study, the author took the initiative to design the appearance of the application to be made. This application is named RSDB (Banjarejo digital trash house) which is an Android mobile-based application. In his research, the author uses the design thinking method, which in this method uses a human-centered or human-centric approach. Then the final result of this research is a prototype design of the RSDB application. from the prototype design that was made, it was tested using the System Usability Scale (SUS) as a measuring tool to get feedback from users and assess how effective the prototype design that had been made was. From the SUS results, a score of